Postnatal breastfeeding education at one week after childbirth: What are the effects?. Issue 2 (April 2019) - Muda, Che Muzaini Che'; Ismail, Tengku Alina Tengku; Jalil, Rohana Ab; Hairon, Suhaily Mohd; Sulaiman, Zaharah; Johar, Nazirah
Abstract: Background: The first week after childbirth is a crucial period for exclusive breastfeeding initiation. Objective: This study aims to determine the association of postnatal breastfeeding education with knowledge, attitude, and exclusive breastfeeding practice at six months after childbirth among women who delivered at two district hospitals in the northeast part of Peninsular Malaysia. Methods: This is a quasi-experimental study design. A newly developed and validated questionnaire was used to determine scoring for baseline and six months after childbirth. The intervention consisted of individualized postnatal breastfeeding education delivered by researchers using flipchart one week after childbirth and breastfeeding diary in addition to usual care. The comparison group received the usual postnatal care by health clinics. Repeated measure analysis of variance and multiple logistic regression analysis were used. Results: A total of 116 participants were included in this study (59 in intervention group and 57 in comparison group). Six months after childbirth, the adjusted mean score of knowledge and attitude of the intervention group were significantly higher than that of the comparison group (p < 0.001 and p = 0.002, respectively). More participants in the intervention group (n = 26, 44.1%) exclusively breastfed their infants compared with 15 (26.3%) in the comparison group (p = 0.046). Postnatal breastfeeding education was significantly associated with exclusive breastfeeding practice six months after childbirth [adjusted odds ratio 2.31; 95% confidence interval: 1.02, 5.14; p = 0.040]. Conclusions: Postnatal breastfeeding education was significantly associated with an improvement in women's knowledge, attitude and exclusive breastfeeding practice six months after childbirth.